Appealing Grammatical Competence: Exploring the Effectiveness of Kahoot! on Young Learners’ Language Proficiency - Marsevani, Maya; Gabriela Micheline Slikker; Zaki, Leil Badrah (Universitas Pendidikan Ganesha, 2024)
The problem addressed by this research is the need for engaging and effective methods to enhance grammar learning among primary students. The research aims of this study were to investigate the feasibility of using Kahoot! as a tool to improve grammar classrooms, especially for young learners, in the only English course that uses books published by the Cambridge University Press. Six elementary students at the A2 level of English participated in one of English course choosen as subject. The data collection methods included pre-tests, post-tests, and semi-structured interviews. Researchers implemented Kahoot! four times during the study. The CAR was carried out in one cycle, as the results from this cycle were deemed sufficient. The instruments used for data collection were pre-tests, post-tests, and semi-structured interviews with the teacher. Data analysis involved comparing pre-test and post-test results to measure improvement and transcribing interview responses to gather qualitative insights. The main results revealed a significant improvement in students' grammar performance. The average score increased from a